Google Classroom as a Tool of Support of Blended Learning for Geography Students (Pedagogy of Higher and Secondary Education, 2018)
Bondarenko O.V., Mantulenko S.V. and Pikilnyak A.V. Google Classroom as a Tool of Support of Blended Learning for Geography Students.The article reveals the experience of organizing blended learning for geography students using Google Classroom, and discloses its potential uses in the study of geography. For the last three years, the authors have tested such in-class and distance courses as “Cartography and Basics of Topography”, “Population Geography”, “Information Systems and Technologies in Tourism Industry”, “Regional Economic and Social World Geography (Europe and the CIS)”, “Regional Economic and Social World Geography (Africa, Latin America, Asia, Anglo-America, Australia and Oceania)”, “Socio-Economic Cartography”.The advantages of using the speciﬁed interactive tool during the study of geographical disciplines are highlighted out in the article. As it has been established, the organization of the learning process using Google Classroom ensures the unity of in-class and out-of-class learning; it is designed to realize eﬀective interaction of the subjects learning in real time; to monitor the quality of training and control the students’ learning achievements in class as well as out of it, etc.The article outlines the disadvantages that should be taken into account when organizing blended learning using Google Classroom, including the occasional predominance of students’ external motivation in education and their low level of readiness for work in the classroom; insuﬃcient level of material and technical support in some classrooms; need for out-of-class pedagogical support; lack of guidance on the content aspect of Google Classroom pages, etc.Through the test series conducted during 2016–2017, an increase in the number of geography students with a suﬃcient level of academic achievements and a decrease of those with a low level of it was revealed.
Keywords: Google Classroom; blended learning; in-class and distance learning